If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7w+1=-9(w-9)
We move all terms to the left:
7w+1-(-9(w-9))=0
We calculate terms in parentheses: -(-9(w-9)), so:We get rid of parentheses
-9(w-9)
We multiply parentheses
-9w+81
Back to the equation:
-(-9w+81)
7w+9w-81+1=0
We add all the numbers together, and all the variables
16w-80=0
We move all terms containing w to the left, all other terms to the right
16w=80
w=80/16
w=5
| 10t^2-3.2t+4=0 | | 16-2r=-3r+6r+1 | | 6x+9=1x+4 | | 6x+9=1x+3 | | 6x+9=1x+2 | | -1/2x=24 | | -b-3(-8-6b)=4+7b | | 5x=3.12-x | | 2x+20+95+x=180 | | 2x+20+x95=180 | | 12^-x+7=13^-5x | | k+6=k+2(k+1) | | 6x=336 | | 35=11x+5 | | -36-p=-2(8+7p)+6 | | 2x20=10 | | -6(5b-5)=2b-34 | | 7x-55=4x+14 | | 10x-156=-2x+72 | | -45+5x=42+2x | | 5-8a=-3+2(1-7a) | | 3x-7=-2x+6x+10 | | 0=5x^2-36x+55 | | 15m+5=210 | | 3(7-7v)=21+8v | | -146-4x=54-12x | | 1/2c=42/5 | | -146-4x=54-12 | | f(-3)=3f(0) | | -2x+(-4x)-18=3 | | h-7=47 | | (3+x)4+10=110 |